Theory of heterogeneous / homogeneous catalytic reaction with presaturation - Coeur-Tourneur, C.; Kopiychenko, D.Yu.; Mchedlov-Petrossyan, P.O. (Вопросы атомной науки и техники, 2012)
In this communication we present a theoretical study of chemical reactions in a system of solid particles, immersed in a fluid environment. Our primary concern here is investigation of the systems of catalytic particles in a liquid media; however with some slight modifications our results are applicable to aerosol systems as well. We consider a second-order reaction, which proceeds both homogeneously in the environment, and heterogeneously at surfaces of catalyst particles. The Langmuir adsorption-desorption kinetics is considered explicitly. For definiteness, we are considering the so-called "three-step mechanism'' of the heterogeneous reaction. Мы рассматриваем одну реакцию второго порядка, которая протекает как гомогенно в окружающей среде, так и гетерогенно на поверхностях каталитических частиц. Адсорбционно-десорбционная ленгмюровская кинетика учитывается явно. Для определённости мы рассматриваем так называемый "трёхступенчатый механизм'' гетерогенной реакции. Ми розглядаємо одну реакцію другого порядку, що протікає як гомогенно в оточуючому середовищі, так і гетерогенно на поверхнях каталітичних частин. Адсорбційно-дисорбційна ленгмюрівська кінетика враховується явно. Для визначеності ми розглядаємо так званий "триступінчатий механізм'' гетерогенної реакції.